Estudio de prospección geoquímica en el Río Pichinal, al Este de Saraguro - Llanes Castillo, Marjorie Judith (2018)
Abstract:The investigation consisted of the geochemical prospecting and mineralogical identification of rocks in outcrops and heavy sediments of the Pichinal River of the Urdaneta parish, Saraguro canton, province of Loja. The purpose is the discovery of the presence of geochemical anomalies of interest in the study area by chemical, mineralogical and statistical analyzes were carried out to obtain maps of the concentration of elements in both rocks and sediments. The analyzes carried out on the samples are X-ray fluorescence (XRF), X-ray diffraction (XRD), microscopic mineralogical identification with the Zoom Stereo for both rocks and magnetic and non-magnetic sediments. Using the data obtained with the FRX test, the statistical analysis was performed to calculate the background, threshold, subanomaly and anomalies. In the Pichinal River anomalie of K2O (33.03%) were obtained in rocks, of Zr (1110) ppm), Mo (194 ppm) and Zn (965 ppm) in heavy magnetic sediments and S (1.16%), Sn (13160 ppm), Cu (138 ppm) Zr (21238 ppm), Mo (2750 ppm) and Zn (150 ppm) in non-magnetic heavy sediments.